Evaluation and management of thyroid nodules in children. Issue 4 (August 2016) - Bauer, Andrew J.; Francis, Gary L.
Abstract : Purpose of review: The review is focused on new information about the presentation and management of thyroid nodules in children and adolescents. Recent findings: Palpable thyroid nodules are uncommon in children but many children have nodules detected by radiologic imaging. How to evaluate them, when to suspect thyroid cancer, and how best to follow apparently benign nodules has become an area of great interest. The American Thyroid Association recently published treatment guidelines for children with thyroid nodules and cancers but much has been learned since that publication. Summary: Personal and family history, ultrasound features, and fine needle aspiration cytology are used to determine the risk of cancer in thyroid nodules, which are then managed according to cancer risk.